A new approach to determine the capture conditions of bark beetles in pheromone-baited traps - Ozcan, Gonca Ece; Cicek, Osman; Enez, Korhan; Yildiz, Mustafa (Informa UK Limited, 2014)
Forests form an organic unity with a great number of organic and inorganic components and tend to maintain the sustainability of their existing balance. However, some factors which adversely affect the balance of nature may interrupt this sustainability. The epidemic which is formed by bark beetles in their spreading region, due to various factors, changes the stability so much that interference is required. One of the most common methods used to monitor these beetles is pheromone-baited traps. The recognition of parameters, such as date (day/month/year), temperature and humidity, when bark beetles are captured in pheromone-baited traps, especially those used for monitoring will help to increase the trap efficiency on land and to develop an effective strategy for combating pests. In this study, an electronic control unit was added to pheromone-baited traps in order to obtain all of the above mentioned parameters. This unit operates with microcontrollers and data related to the parameters is saved in a storage unit. This is triggered by the beetle at the moment it is captured in the trap. A photovoltaic system was used to meet the energy needed for the system functioning and to complete the counting process in due time.
Keywords: Article; Biodiversity and Ecosystems; 14. Life underwater; 15. Life on land; 7. Clean energy